2010
DOI: 10.1111/j.1540-8167.2010.01772.x
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis Impairs the Protective Role of hERG K+ Channels Against Premature Stimulation

Abstract: During acidosis the contribution of I(hERG) to action potential repolarization is reduced and hERG may be less effective in counteracting proarrhythmogenic depolarizing stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(85 citation statements)
references
References 30 publications
7
78
0
Order By: Relevance
“…2B. This decrease in phase 2 amplitude of MAP is consistent with previous reports (9,19,20), which has been ascribed to a decrease in plateau-phase Ca 2+ influx (19,21). Meanwhile, with regard to the shortening of MAP duration, some studies reported that a decrease in extracellular pH shortens the action potential duration (22 -25), but the others described opposite results (26,27).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…2B. This decrease in phase 2 amplitude of MAP is consistent with previous reports (9,19,20), which has been ascribed to a decrease in plateau-phase Ca 2+ influx (19,21). Meanwhile, with regard to the shortening of MAP duration, some studies reported that a decrease in extracellular pH shortens the action potential duration (22 -25), but the others described opposite results (26,27).…”
Section: Discussionsupporting
confidence: 80%
“…Meanwhile, with regard to the shortening of MAP duration, some studies reported that a decrease in extracellular pH shortens the action potential duration (22 -25), but the others described opposite results (26,27). It has been reported that under acidic condi- tions, H + directly binds to I Kr and I Ca channels, resulting in their current inhibitions (11,19,20,28). Inhibition of I Kr channels causes the prolongation of MAP duration, whereas inhibition of I Ca channels leads to its shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple groups have also reported that the changes in deactivation and suppression of G max had different pH sensitivities (26,64,262), and this likely explains some of the discrepancies between studies in which different pH ranges were used. Nevertheless, the overall effect is to cause a reduction of the amount of I Kr that will flow during the action potential (152), which contributes to the action potential prolongation observed during acidosis (63).…”
Section: Acidosismentioning
confidence: 99%
“…Investigations into the effects of acidosis on hERG channel function demonstrate an extracellular proton-induced reduction in peak current amplitude (1,4,27,54,57) and an acceleration of deactivation (1,2,4,25,27,54,57); action potential simulation studies suggest that these actions cause a predisposition to arrhythmia by reducing the protection against premature stimulation (13). Furthermore, extracellular acidosis has recently been shown to reduce the binding affinity of some antiarrhythmic drugs (15).…”
mentioning
confidence: 99%